Finding the way: Guomindang discourse, Confucius, and the challenges of revolutionary traditionalism in China, 1919-1934 - Bowles, D (2016)
Between 1919 and 1934, as members of China's Guomindang (Nationalist Party) struggled to take control of and transform the country, they increasingly appropriated language and symbols associated with the fallen Qing Dynasty. At the same time, these were accompanied in party discourse by radical appeals that included strong critiques of China's past. In this they were far from unique: studies of nationalisms around the world have found them to combine appeals to the new and the old. Yet in China this combination incited particular controversy, as Guomindang members and others, wrestling with the cultural legacy of the empire, put forward powerfully radical critiques not only of the culture of the past but also of traditionalist appeals to it. The result was distinctive textual practices I term 'revolutionary traditionalism', which appropriated cultural elements of the imperial orthodoxy while reconciling these appropriations with radical language. Yet this revolutionary traditionalism could not unproblematically form a unified modern nationalist orthodoxy. Radical and traditionalist positions in regard to culture recurred through power struggles within and beyond the party. Through these struggles, by the end of the 1920s revolutionary traditionalism came to characterise the new Nationalist Government formed by Guomindang members in Nanjing. While like other nationalists Guomindang members reinvented the language and symbols to which they appealed, however, the case of Confucius shows that they could not unilaterally control these reinterpretations. The central place of Confucius in national culture was established through a process of negotiation, as groups identifying themselves as 'Confucian' petitioned the state, appropriating its own traditionalist discourse, for recognition and commemoration. Yet these Confucians, pursuing their own often religious agendas, also cast doubt on the authenticity of the state’s commitment. Revolutionary traditionalism thus remained unstable, repeatedly challenged both from radical and traditionalist positions.